2021
DOI: 10.3390/mi12070773
|View full text |Cite
|
Sign up to set email alerts
|

Smart Textiles for Visible and IR Camouflage Application: State-of-the-Art and Microfabrication Path Forward

Abstract: Protective textiles used for military applications must fulfill a variety of functional requirements, including durability, resistance to environmental conditions and ballistic threats, all while being comfortable and lightweight. In addition, these textiles must provide camouflage and concealment under various environmental conditions and, thus, a range of wavelengths on the electromagnetic spectrum. Similar requirements may exist for other applications, for instance hunting. With improvements in infrared sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 73 publications
0
38
0
Order By: Relevance
“…† The results suggested that it is possible to manufacture surfaces and textile fabrics with low gloss (less than 10%) and low reflectance (R b < 3), independent of the lignin content. These properties (low gloss and radiance) are essential for textile camouflage, 79 thermal protective clothing, 80 and thermal energy textiles using phase change materials. 81 The high stretchability of the filaments under wet conditions encouraged us to test LCF for underwater applications in marine environments.…”
Section: Valorization By Ionic Liquid Dissolutionmentioning
confidence: 99%
“…† The results suggested that it is possible to manufacture surfaces and textile fabrics with low gloss (less than 10%) and low reflectance (R b < 3), independent of the lignin content. These properties (low gloss and radiance) are essential for textile camouflage, 79 thermal protective clothing, 80 and thermal energy textiles using phase change materials. 81 The high stretchability of the filaments under wet conditions encouraged us to test LCF for underwater applications in marine environments.…”
Section: Valorization By Ionic Liquid Dissolutionmentioning
confidence: 99%
“…Another area of application for intelligent textiles is military clothing, in which the health status of soldiers is continuously monitored. Integrated sensors in the helmet and a comprehensive vital sign system register the person's position and movement as well as heart and breathing rates [78]. In addition, the fluid intake, skin temperature measurement and sleep behavior are constantly checked and displayed on the monitor.…”
Section: Military Protective Clothingmentioning
confidence: 99%
“…Building on past works, the focus of this study is to develop predictive models using COMSOL Multiphysics [ 30 ] to inform design decisions when manufacturing polyethylene (PE)‐based micro‐ and macro‐scale metamaterials for passive and active thermal camouflaging applications within the MIR wavelength (5–16 µm). PE is the polymer of choice for this study due to its low emissive properties, [ 29,31,32 ] ability to be woven into fibers for smart textile applications, [ 33 ] elastic durability, [ 34 ] and high IR transparency. [ 35 ] For the first time in the literature: (1) PE‐based patterned metamaterials (specifically, micro‐ and macro‐scale designs) for passive and active thermal management solutions are proposed, (2) a lenticular lens macro‐scale design in various configurations (e.g., single‐layered and multi‐layered systems) is explored for efficient thermal management, (3) active solutions to thermal radiation control are introduced where elastic properties of PE are used to dynamically change the geometrical aspect ratio of the unit cells of metamaterials, and (4) preferable configurations for micro‐scale post design (post height, width, and spacing) are proposed.…”
Section: Introductionmentioning
confidence: 99%
“…Building on past works, the focus of this study is to develop predictive models using COMSOL Multiphysics [30] to inform design decisions when manufacturing polyethylene (PE)-based micro-and macro-scale metamaterials for passive and active thermal camouflaging applications within the MIR wavelength (5-16 µm). PE is the polymer of choice for this study due to its low emissive properties, [29,31,32] ability to be woven into fibers for smart textile applications, [33] elastic durability, [34] and high IR transparency. [35] For the first time in the literature:…”
Section: Introductionmentioning
confidence: 99%